Profiling the trapped and deactivating species on HZSM-5 zeolite during 1-butene oligomerization - Sepideh Izaddoust; Idoia Hita; Timo Kekäläinen; José Valecillos; Janne Jänis; Pedro Castaño; Eva Epelde (Fuel Processing Technology, 2025)
The transformation of 1-butene into valuable fuels using HZSM-5 zeolite catalysts is significantly hindered by deactivation caused by deposited species and coke formation. This work delves into the entrapment, formation, and growth of these species during 1-butene oligomerization at 275–325 °C, 1.5–40 bar, and space-times of 2–6 gcat h molC−1. We have employed an extensive characterization of the used catalysts, integrating conventional techniques with high-resolution mass spectrometry (Fourier Transform Ion Cyclotron Resonance Mass Spectrometry, FT-ICR MS). This advanced technique provides a detailed molecular-level analysis of these species. Our findings reveal that higher pressures promote oligomerization, resulting in an increased accumulation of trapped oligomer species. Conversely, higher temperatures facilitate the cracking of these oligomers into lighter fractions or their further conversion into coke molecules through condensation reactions. This dual behavior underscores the complex interplay between temperature and pressure in influencing the deactivation pathways. By understanding the overall reaction mechanism and the formation and growth patterns of trapped and deactivating species, we can develop strategies to mitigate catalyst deactivation, ultimately leading to more efficient industrial applications.